Hydrothermal synthesis of an expanded perlite based lightweight composite for indoor humidity regulating. (10th October 2022) - Yue, Liang; Qiu, Pengcheng; Zhang, Yafei; Miao, Jiajun; Jing, Zhenzi
Graphical abstract: Highlights: A lightweight tough composite could be synthesized from EP for humidity regulating. Tobermorite formation could enhance strength and improve porosity of the material. CaCl2 addition could promote porosity and improve moisture adsorption/desorption. CMC formation could form crosslinked networks thus improving humidity regulation. Both CaCl2 and CMC addition had large effect on regulating humidity synergetically. Abstract: A lightweight and tough indoor construction material has been synthesized hydrothermally from expanded perlite (EP) with indoor humidity regulation for high-rise buildings. Due to the low-temperature (≤473.15 K) hydrothermal treatment, the original porosity of EP was remained in the matrix to serve a low density (<0.900 g/cm 3 ). The formation of CSH and tobermorite could not only enhance the flexural strength of the composite (greater than 16.0 MPa), but also improve its porosity. The CaCl2 addition had a capability of promoting the porosity and improving the moisture adsorption/desorption capacity. The CaCl2 solution could make more moisture adsorbed in pores and more pores possess the humidity self-regulation ability. The CMC addition could generate crosslinked networks and high osmotic pressure to promote humidity self-regulating performance greatly. Furthermore, the addition of both CaCl2 and CMC exerted a synergetic effect to further reinforce moisture adsorption capacity (∼380 g/m 2 ).